Triosephosphate isomerase from baker's yeast - ribozyme versus protein - ON Solovjeva (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2020)
It was previously shown that in baker's yeast Saccharomyces cerevisiae, transketolase can exist not only free, but in complex with RNA. The complex does not possess transketolase activity [N.K. Tikhomirova, G.A. Kochetov, A new method of isolation and a new form of transketolase from baker's yeast, Biokhimiia 56 (1991) 1123-1130].  We discovered that this RNA is a ribozyme which catalyzes the interconversion of glyceraldehyde 3-phosphate (G3P) and dihydroxyacetone 3-phosphate (DHAP), i.e. acting as triosephosphate isomerase (TPI). It also catalyzes an unusual reaction of ribose 5-phosphate (R5P) decomposition to G3P ​​and erythrose. TPI-ribozyme was found in baker's yeast not only in complex with transketolase, but also in free form. Transketolase-RNA complex was easily isolated on an immunoaffinity column with antibodies to transketolase. TPI-ribozyme consists of 87 nucleotides and has a molecular weight of 26.6 kDa. The optimum of pH-activity is 7.5 for DHAP, 6.7 for R5P and 9.0 for G3P. Km and Vmax are accordingly 0.29 mM and 2.6 U/mg for DHAP, 22 mM and 0.65 U/mg for R5P, 0.05 mM and 4.3 U/mg at pH 7.6 and 0.11 mM and 16 U/mg at pH 9.0 for G3P. These kinetic characteristics are the same for free RNA and in the complex with transketolase. Ki for RNA binding to transketolase was 1.0 μM. Accordingly, the TPI-ribozyme performs a dual function - it shows TPI activity and blocks the work of transketolase, thereby switching the metabolic process to glycolysis. The location of the TPI-ribozyme gene is determined. Blocking the activity of transketolase by ribozyme may be of practical importance in medicine, particularly, in cancer therapy.